Advanced vaccinomic, immunoinformatic, and molecular modeling strategies for designing Multi- epitope vaccines against the Enterobacter cloacae complex - Alhassan, Hassan H. (Frontiers in Immunology, 2024)
The increasing and ongoing issue of antibiotic resistance in bacteria is of huge concern globally mainly to health care facilities. It is now very crucial to develop a vaccine for therapeutic and preventive purposes against the bacterial species causing hospital-based infections. Among many antibiotics bacterial pathogens Enterobacter cloacae complex (ECC) containing six species including E. Colcae, E. absuriae, E. kobie, E. hormaechei, E. ludwigii and E. nimipressuralis are the dangerous issue to public health and may make the situation more worsen. Vaccination plays a vital role in prevention of the infections and infectious diseases. This research highlighted the construction and designing of a multi-epitope vaccine for E. cloacae complex retrieving their complete sequenced proteome. The retrieved proteome was assessed to opt for potential vaccine candidates using immmunoinformatics tools. Both B and T-cell epitopes were predicted in order to create both humoral and cellular immunity, further scrutinized for antigenicity, allergenicity, water solubility, and toxicity analysis. The final potential epitopes were subjected to population coverage analysis. Major histocompatibility complex (MHC) class combined, and MHC Class I and II world population coverage was obtained as 99.74%, and 98.55% respectively while a combined 81.81% was covered, Multi epitope peptide-based vaccine construct consisting of the adjuvant, epitopes, and likers was subjected to the ProtParam tool to calculate its physiochemical properties. The total amino acids were 236, molecular weight was 27.64kd and vaccine construct was stable also with an instability index of 27.01. The GRAVY (hydrophilicity) value obtained was -0.659 being more negative depicting the hydrophilic character. It was non-allergen antigenic with an antigenicity of 0.8913. The vaccine construct was further validated for binding efficacy with immune cell receptors MHC-I, MHC-II Toll-like receptor (TLR)-4. The molecular docking results depict that the designed vaccine has good binding potency with immune receptors crucial for antigen presentation and processing. Overall, we observed that the designed vaccine construct can evoke a proper immune response and the construct could help the experimental researchers in the formulation of the vaccine against targeted pathogen.